MENGUKUR PERKEMBANGAN PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DALAM RANGKA MENDUKUNG PELAKSANAAN PEMBANGUNAN DAERAH DI PROVINSI NUSA TENGGARA BARAT (NTB) - SAHRUDIN sahrudi RUDI (Cakrawala Management Business Journal, 2021)
Abstract The development of Regional Original Revenue Revenue (PAD) of West Nusa Tenggara (NTB) Province seen from the development of targets and realization in 2014-2018 an average of 102.72%, Local Own Revenue (PAD) to the 2014 Regional Budget (APBD) - 2018 an average of 36.18% is included in the Consultative or moderate pattern where the intervention of the central government begins to decrease because the approach is less capable of implementing regional autonomy and development, and in the aspect of growth in the realization of Regional Original Revenue (PAD) an average of 14, 87% from 2014-2018. The Provincial Government of West Nusa Tenggara (NTB) is expected to strive to further increase Regional Original Income (PAD) by optimizing all revenue instruments that have not contributed positively, as stipulated in the provisions or regulations relating to regional revenues in the context of implementing regional autonomy, realizing The level of independence in the implementation of regional autonomy is a must for local governments in encouraging the process of accelerating the development of West Nusa Tenggara (NTB) Province Keywords: Development PAD to words APBD